2002
DOI: 10.1017/s1357729800052838
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maize starch or soya-bean oil as energy sources in lactation on sow and piglet performance in association with sow metabolic state around peak lactation

Abstract: The effects of different energy sources in the lactation diet on sow and piglet performance were assessed in association with effects on the metabolic state of the sow around peak lactation. Either maize starch (S) or soya-bean oil (F) was added to a basal diet to provide 0·34 of total digestible energy (DE) intake, such that the experimental diets provided the same daily intakes of DE and crude protein. Twenty-four multiparous sows were allocated between two groups at farrowing, each given one of the two diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…It appears the amount or the nature of the lysozyme supplementations has not been adequate to change the milk composition. It has been found that lysozyme supplementation does not change the composition of milk unlike some nutrients, such as fat (Chapman et al, 2000;Jones et al, 2002;Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It appears the amount or the nature of the lysozyme supplementations has not been adequate to change the milk composition. It has been found that lysozyme supplementation does not change the composition of milk unlike some nutrients, such as fat (Chapman et al, 2000;Jones et al, 2002;Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the backfat thickness loss during lactation was significantly higher in the fat-supplemented sows in trial 1, which corresponds to a deteriorated energy balance as already reported by Schoenherr et al (1989) andvan den Brand et al (2000). Such results indicate that the extra energy intake supplied by lipids is of little interest for the sow itself as most fatty acids are transferred to the mammary glands and incorporated in milk lipids (Boyd et al, 1978;Jones et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This condition was met in trial 1 and resulted in a higher increase of ADG of litters than in trial 2 in which no extra fat was provided to sows before farrowing. According to Jones et al (2002) and Ramaekers (2003), litter growth performance is not influenced by fat content in the lactation diet when no creep feed is provided, and piglets are fatter at weaning. In our trials, creep feed was supplied during the last 3 weeks of lactation and a higher intake was observed in the L0 litters than in the L5 ones.…”
mentioning
confidence: 99%
“…Isolator reared pigs had body weights slightly lower than typically seen for sow reared pigs (Jones et al 2002).…”
Section: ---------------------------mentioning
confidence: 71%